Low-Temperature CH4 Reforming and Water Splitting with Activated NiO/CeO2 as Oxygen Carrier - Han, Chunli; Yoko, Akira; Chang, Yi‑Ping; Harder, Manuel; Ninomiya, Kakeru; Nishibori, Maiko; Yin, Zhong; Taufik, Ardiansyah; Ohara, Satoshi; Adschiri, Tadafumi (Nano-Micro Letters, 2026)
Energy-efficient and selective hydrocarbon reforming techniques are crucial for a sustainable future. This study develops a highly active and selective NiO/CeO2 oxygen carrier (OC) for low-temperature chemical looping partial oxidation of methane and water splitting. By using cubic CeO2 (cCeO2) as support and precisely tailoring the size and electronic structure of Ni active sites, simultaneous low-temperature CH4 activation and high syngas selectivity (CH4-to-syngas selectivity: > 98.5%) were achieved, effectively suppressing CH4 cracking and complete oxidation. The as-synthesized NiO/cCeO2 OCs operate efficiently at 600 °C, significantly lower than the conventional temperature, 800–900 °C. Nearly pure H2 is produced in the water splitting step. High selectivity eliminates the need for additional gas separation and purification units. It is noteworthy that reaction-driven OC activation pretreatment plays a significant role in achieving the stable low-temperature activity, which leads to the moderate aggregation (10–20 nm) of Ni species and transforms Ni2+ from a low-spin state into a high-spin state. The OC structural evolution during reaction, key active sites responsible for water splitting, and the support effect are systematically investigated. The highly precise microstructural manipulation strategies outlined here are expected to guide further advancements in high-performance low-temperature OCs for chemical looping processes. Highlights: 1 Low-temperature (≤600 °C) CH4 activation and high syngas selectivity (>98.5%, H2/CO2) were simultaneously achieved using the activated NiO/cCeO2 oxygen carrier. Nearly pure H2 was produced during the water splitting step. 2 Synergistic advantages of low operating temperature and high selectivity significantly enhance the energy efficiency of chemical looping CH4 reforming and water splitting process. 3 Precise control over the size and density of Ni sites and activation and structural evolution of NiO/cCeO2 were systematically investigated.